KONSEP PENANAMAN NILAI-NILAI PENDIDIKAN ISLAM PADA BUMD AIR MINUM TIRTA INTAN GARUT - Rowi Karim, Aja (Program Studi Pendidikan Agama Islam, 2024)
This research is motivated by educational activities in companies that must be carried out to get a healthy company performance assessment. The training education program at the company does not merely fulfill skill skills but spiritual strengthening of employees through Islamic education as a process of achieving a degree of faith, piety, discipline to work that not only works for worldly gain but works for the afterlife as well. The purpose of this research is to identify the concept of Cultivating Islamic Education Values and the success in Cultivating Islamic Education Values at the Regional Owned Enterprises (BUMD) Tirta Intan Garut Drinking Water. The framework of this research refers to Max Weber's theory that in the capitalist soul work is a useful and correct activity, because the activity itself is not solely for material pleasure. This research uses a qualitative approach with a descriptive method of field research (field research) research location at the BUMD company Tirta Intan Garut Drinking Water Jl. Raya Bayongbong Km 3. Kp. Gandasari Cilawu Garut Regency. The collection technique begins with observation, interviews and documentation. After that, it was analyzed by reducing data (data reduction), presenting data (data display), and drawing conclusions (conclusion drawing/verification). The results showed that the cultivation of the values of tawhid, worship, morals at BUMD Tirta Intan Garut Drinking Water. Implemented through non-formal religious activities without the regulation of BUMD Drinking Water, but rather a routine activity carried out consistently without a program but focusing on direct activities in the form of Islamic education activities informed through circulars, announcements, invitations from leaders that must be carried out by employees when working, namely at every morning and evening apples, the value of tawhid, worship, morals becomes the main theme of the briefing. Implementation related to the value of Islamic religious education is in the form of mandatory prayers in congregation, praying before doing activities, alms, compensation, greeting and respecting each other, Umrah activities, qurban activities, UP Zis, and religious studies..